2019
DOI: 10.1111/mmi.14435
|View full text |Cite
|
Sign up to set email alerts
|

Surface resistance to SSVs and SIRVs in pilin deletions of Sulfolobus islandicus

Abstract: Characterizing the molecular interactions of viruses in natural microbial populations offers insights into virus–host dynamics in complex ecosystems. We identify the resistance of Sulfolobus islandicus to Sulfolobus spindle‐shaped virus (SSV9) conferred by chromosomal deletions of pilin genes, pilA1 and pilA2 that are individually able to complement resistance. Mutants with deletions of both pilA1 and pilA2 or the prepilin peptidase, PibD, show the reduction in the number of pilins observed in TEM and reduced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 49 publications
1
29
0
Order By: Relevance
“…1a, b). Consequently, the filaments appear to serve as the primary receptors for SSRV1 and PFV2, as has been demonstrated for some other archaeal viruses [16][17][18] .…”
Section: Resultsmentioning
confidence: 64%
See 2 more Smart Citations
“…1a, b). Consequently, the filaments appear to serve as the primary receptors for SSRV1 and PFV2, as has been demonstrated for some other archaeal viruses [16][17][18] .…”
Section: Resultsmentioning
confidence: 64%
“…For instance, mass-spectrometry analysis of a crude sample typically yields too many potential candidate proteins for unequivocal identification, whereas some proteins are not amenable to standard tryptic digestion, as has been shown recently for the pili of S. islandicus 26 . Pili appear to be a common receptor for hyperthermophilic archaeal viruses and have been previously shown to be recognized by rudiviruses SIRV2 and SIRV8 16,17 , and turrivirus STIV 18 . Here we have shown that members of yet another family of archaeal viruses, the Tristromaviridae, also bind to the host cells via T4P.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Filamentous surface structures are well known primary anchor points for several viruses infecting bacteria (Poranen et al, 2002;Mäntynen et al, 2019). Recent data suggests that a few crenarchaeal viruses also tether to filamentous surface structures (Quemin et al, 2013;Hartman et al, 2019;Rowland et al, 2020). A hallmark of archaeal surface structures is the widespread similarity to bacterial type IV pili.…”
Section: Pilinsmentioning
confidence: 99%
“…This experimental and theoretical evidence for advantages of surface modification may entail strong fitness costs under natural conditions because mutations in surface receptors such as those in flagella or pili can be detrimental for microbial movement and biofilm formation [21]. Investigations of natural populations have indeed shown that surface resistance is costly in the wild [27,28]. These observations underlie the need for complementing experimental approaches by developing theory on the kinds of 'macroscopic', whole system, diversity patterns expected under 'microscopic' CRISPR-induced coevolutionary processes.…”
Section: Introductionmentioning
confidence: 99%